2015
DOI: 10.1007/s10439-015-1429-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–Structure Interaction Model of a Percutaneous Aortic Valve: Comparison with an In Vitro Test and Feasibility Study in a Patient-Specific Case

Abstract: Transcatheter aortic valve replacement (TAVR) represents an established recent technology in a high risk patient base. To better understand TAVR performance, a fluid-structure interaction (FSI) model of a self-expandable transcatheter aortic valve was proposed. After an in vitro durability experiment was done to test the valve, the FSI model was built to reproduce the experimental test. Lastly, the FSI model was used to simulate the virtual implant and performance in a patient-specific case. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 41 publications
3
81
0
1
Order By: Relevance
“…First, the polymeric valve was modelled as a homogeneous, linear elastic and isotropic material. The simplification of the polymer as a linear elastic model was used to stabilize the simulation due to the complexity of the contact among the leaflets as in Wu et al (2016)). In this regard, specific anisotropic mechanical behaviour models will be adopted in the future by implementing a new constitutive law including the optimisation of the fibre direction in the polymer (Serrani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the polymeric valve was modelled as a homogeneous, linear elastic and isotropic material. The simplification of the polymer as a linear elastic model was used to stabilize the simulation due to the complexity of the contact among the leaflets as in Wu et al (2016)). In this regard, specific anisotropic mechanical behaviour models will be adopted in the future by implementing a new constitutive law including the optimisation of the fibre direction in the polymer (Serrani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a number of computational studies on prosthetic heart valves have been performed neglecting the blood flow across the prosthetic valve but simply considering hydrostatic pressures acting on the structure domain (Gunning et al, 2014, Wang et al, 2015, Morganti et al, 2014). At the same time, the number of studies considering fluid-structure interaction is increasing, for instance, studies on the behaviour of the aortic root in the presence of native valves (De Hart et al, 2003a, Marom et al, 2012, Ranga et al, 2006, Sturla et al, 2013, Weinberg and Kaazempur Mofrad, 2007), and a few on prosthetic valves (Bavo et al, 2016, Wu et al, 2016, Borazjani, 2013). However, with exception of the work by Wu et al, none of the previous works has included experimental validations.…”
Section: Introductionmentioning
confidence: 99%
“…This extension naturally suggests application to FSI, and a recent series of papers by Huang, Sung, and collaborators has demonstrated that feedback forcing is a robust and accurate approach for the simulation of light flexible structures immersed in incompressible flows [114118]. A similar immersed boundary approach has been used in the commercial code LS-DYNA [119] for decades, to study automobile airbag inflation and other challenging FSI problems [120–123], including heart valve simulation [7, 13, 21, 124]. LS-DYNA documentation refers to this capability as the “constrained Lagrange in solid” formulation.…”
Section: Mathematical Model and Immersogeometric Discretization Ofmentioning
confidence: 99%
“…Practical instances of this problem include parachute dynamics [1, 2], flying insects [3, 4], and the valves regulating blood flow through the heart [521]. The last topic mentioned, heart valve fluid–structure interaction (FSI), has received much attention in the past few years due to both the unique combination of challenges it poses to computational mechanicians and the practical benefits to be reaped from improved understanding of heart valve FSI dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercial software LS-DYNA have been used for FSI simulations of bioprosthetic and native aortic valves 21,24,191,230 since the late 1990s with immersed boundary methods. The time-explicit procedures used by LS-DYNA result in severe Courant—Friedrichs—Lewy conditions that limit the maximum stable time step size in hemodynamic computations, because blood is nearly incompressible, rendering the problem effectively parabolic.…”
Section: Computational Simulationsmentioning
confidence: 99%